Analisis Komunikasi Eksternal Pemerintahan dalam Pembangunan Infrastruktur Jalan di Liang Melas Datas Kabupaten Karo - Sembiring, Ruth Agnesia (Journal of Governance Innovation, 2024)
This research analyzes the governmental external communication in the development of road infrastructure in Liang Melas Datas (LMD), a region consisting of six villages and three hamlets located in three sub-districts in Karo Regency of North Sumatra. The road that has been damaged for around twenty years has made the surrounding communities difficult to transport their agricultural produce to the market. The communities made themselves the information sender by delivering three tons of Siam orange (Citrus Nobilis) to the President of Indonesia as a gift along with their representatives to meet him in December of 2021. This qualitative descriptive research employs two types of data. As the primary was acquired from interviews with the message sending initiator, the secondary was gathered from mass media, the government’s website, YouTube channels, the Karo people communities’ Instagram accounts, and the government’s official documents. Here governmental external communication and the concept of development communication were used as the tools of analysis. This study finds the message communicator is Efendra Sembiring (ES) who initiated the idea of delivering the gift to the president. Delivery of gifts to the president without the help of any political elite. The media for the message are social media, direct meeting, and local mass media. The people of LMD are able to use their local potentials as instruments to deliver the information. The effect is that the people of LMD have more knowledge and different attitude and behavior after receiving the idea of ES. The central government was also affected, proven by the acceleration in the development of road infrastructure which was also directly observed by the president through his visit in February 2022.